Zooming in on monetary policy: The labor share and production dynamics of two million firms - Jan Philipp Fritsche; Lea Steininger (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Conditional on a contractionary monetary policy shock, the labor share of value added is expected to decrease in the basic New Keynesian model. By providing firm-level evidence, we are first to validate this proposition. Using local projections and high dimensional fixed effects, we show that a one standard deviation contractionary monetary policy shock decreases firms' labor share by 0.4 percent, on average. However, reactions are heterogeneous along two dimensions: The labor share is most informative to discriminate firms by their response in payroll expenses, firms' leverage is most informative to discriminate by their response in value added. We inform the policy debate on transmission and redistribution effects of monetary policy.
Keywords: D22; D31; E23; E32; C52; 330; Monetary policy; firm heterogeneity; labor share; financial frictions; DSGE model validation